Abnormal Curves on the Goursat Systems of R𝑛 - Mohamad H. Cheaito; Hassan Zeineddine (International Journal of Mathematics and Mathematical Sciences)
We study the abnormal and the rigid curves of the 2-distributions of 𝐑𝑛 satisfying everywhere the Goursat condition. We give the directions for the rigid and the abnormal curves when the systems satisfy the strong Goursat condition or when they have a singularity of order 2 in each dimension.